Inhibition of acid sphingomyelinase increases regulatory T cells in humans. Issue 2 (5th March 2021) - Wiese, Teresa; Dennstädt, Fabio; Hollmann, Claudia; Stonawski, Saskia; Wurst, Catherina; Fink, Julian; Gorte, Erika; Mandasari, Putri; Domschke, Katharina; Hommers, Leif; Vanhove, Bernard; Schumacher, Fabian; et al.
Abstract: Genetic deficiency for acid sphingomyelinase or its pharmacological inhibition has been shown to increase Foxp3 + regulatory T-cell frequencies among CD4 + T cells in mice. We now investigated whether pharmacological targeting of the acid sphingomyelinase, which catalyzes the cleavage of sphingomyelin to ceramide and phosphorylcholine, also allows to manipulate relative CD4 + Foxp3 + regulatory T-cell frequencies in humans. Pharmacological acid sphingomyelinase inhibition with antidepressants like sertraline, but not those without an inhibitory effect on acid sphingomyelinase activity like citalopram, increased the frequency of Foxp3 + regulatory T cell among human CD4 + T cells in vitro . In an observational prospective clinical study with patients suffering from major depression, we observed that acid sphingomyelinase-inhibiting antidepressants induced a stronger relative increase in the frequency of CD4 + Foxp3 + regulatory T cells in peripheral blood than acid sphingomyelinase-non- or weakly inhibiting antidepressants. This was particularly true for CD45RA − CD25 high effector CD4 + Foxp3 + regulatory T cells. Mechanistically, our data indicate that the positive effect of acid sphingomyelinase inhibition on CD4 + Foxp3 + regulatory T cells required CD28 co-stimulation, suggesting that enhanced CD28 co-stimulation was the driver of the observed increase in the frequency of Foxp3 + regulatory T cells among human CD4 + T cells. In summary, the widely induced pharmacological inhibition of acid sphingomyelinase activity in patients leads to an increase in Foxp3 + regulatory T-cell frequencies among CD4 + T cells in humans both in vivo and in vitro . Abstract : In their study, Wiese et al. found that pharmacological inhibition of acid sphingomyelinase with antidepressants such as sertraline or amitriptyline increased the proportion of Foxp3 + regulatory T cells among human CD4 + T cells both in cell culture in vitro as well as in vivo in patients treated for major depression. Graphical Abstract: